PERGURUAN TINGGI DALAM ERA GLOBALISASI: PERSPEKTIF BALANCE SCORECARD - Walean, Ronny Hansje (JBE (Journal of Business and Economics); Volume 6 No.1, 2007 JBE UNKLAB, 2007)
The term “Globalization” has acquired considerable emotive force. Some view it as a process that beneficial – a key to future world economic development. Others regard it with hostility, even fear, believing that it-increases inequality within and between nations, threatens organization, employment, living standard and progress. The crisis in the emerging-markets have made it quite evident - - that opportunities of globalization do not come without risks. –companies- can survive from a4een  -competition by carefully using best methods to evaluate companies performance so the alternatives that provides-top management with the instrument to navigate the performance in four balanced perspectives: customer, financial, internal business processes , and learning and growth.